Photoelectrochemical properties of bismuth-doped titanium oxide electrodes - Park, S.-Y.; Cho, B.-W.; Yun, K.-S.; Lee, E.-C. (Kluwer Academic Publishers, 1994)
With the aim of obtaining TiO2 films with increased photoresponse titanium metal was alloyed with bismuth and then directly oxidized. The free energy efficiencies of the Ti-Bi oxide increased four times by increasing the bismuth content up to 10 wt %. The spectral response of the Ti -Bi oxides was slightly shifted toward the visible region with respect to the response of TiO2, and their Eg were observed to be in the range 2.87-3.0 eV. ？ 1994 Chapman & Hall.